FAKTOR-FAKTOR YANG DIPERTIMBANGKAN KONSUMEN PADA PEMBELIAN SEPEDA MOTOR MEREK YAMAHA DI KOTA PALU - Sufriyatna, Edwin (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2017)
This study aims to determine some factors considered by consumers prior to purchasing Yamaha motorcycles in Palu City. Type of study is exploratory with 105 respondents who bought Yamaha motorcycle in Palu City. Data collection techniques include observation, interview, and questionnaire. The tool for factor analysis is SPSS program 22.0. The results show that factors such as product, price, friend suggestion, promotion, product quality, service quality, advertisement, family suggestion, brand, lifestyle, brochure, and design were considered by consumers in buying Yamaha motorcycles in Palu City.